Specific training for LESS surgery results from a prospective study in the animal model - Marchini,Giovannni Scala (2016)
ABSTRACT Objective to prospectively evaluate the ability of post-graduate students enrolled in a laparoscopy program of the Institute for Teaching and Research to complete single port total nephrectomies. Materials and Methods 15 post-graduate students were enrolled in the study, which was performed using the SILStm port system for single-port procedures. All participants were already proficient in total nephrectomies in animal models and performed a left followed by a right nephrectomy. Analyzed data comprised incision size, complications, and the time taken to complete each part of the procedure. Statistical significance was set at p<0.05. Results All students successfully finished the procedure using the single-port system. A total of 30 nephrectomies were analyzed. Mean incision size was 3.61 cm, mean time to trocar insertion was 9.61 min and to dissect the renal hilum was 25.3 min. Mean time to dissect the kidney was 5.18 min and to complete the whole procedure was 39.4 min. Total renal hilum and operative time was 45.8% (p<0.001) and 38% (p=0.001) faster in the second procedure, respectively. Complications included 3 renal vein lesions, 2 kidney lacerations and 1 lesion of a lumbar artery. All were immediately identified and corrected laparoscopically through the single-port system, except for one renal vein lesion, which required the introduction an auxiliary laparoscopic port. Conclusion Laparoscopic single-port nephrectomy in the experimental animal model is a feasible but relatively difficult procedure for those with intermediate laparoscopic experience. Intraoperative complications might be successfully treated with the single-port system. Training aids reducing surgical time and improves outcomes.